Methylation of ribosomal RNA by NSUN5 is a conserved mechanism modulating organismal lifespan - Schosserer, Markus; Minois, Nadege; Angerer, Tina B.; Amring, Manuela; Dellago, Hanna; Harreither, Eva; Calle-Perez, Alfonso; Pircher, Andreas; Gerstl, Matthias Peter; Pfeifenberger, Sigrid; Brandl, Clemens; Sonntagbauer, Markus; et al. (Nature Communications, 2015)
Several pathways modulating longevity and stress resistance converge on translation by targeting ribosomal proteins or initiation factors, but whether this involves modifications of ribosomal RNA is unclear. Here, we show that reduced levels of the conserved RNA methyltransferase NSUN5 increase the lifespan and stress resistance in yeast, worms and flies. Rcm1, the yeast homologue of NSUN5, methylates C2278 within a conserved region of 25S rRNA. Loss of Rcm1 alters the structural conformation of the ribosome in close proximity to C2278, as well as translational fidelity, and favours recruitment of a distinct subset of oxidative stress-responsive mRNAs into polysomes. Thus, rather than merely being a static molecular machine executing translation, the ribosome exhibits functional diversity by modification of just a single rRNA nucleotide, resulting in an alteration of organismal physiological behaviour, and linking rRNA-mediated translational regulation to modulation of lifespan, and differential stress response.
Gesehen am 13.07.2020